Influence of male density on reproductive fitness of female rice weevil Sitophilus oryzae L (Coleoptera Curculionidae) - Flay, C.; Wang, Q. (New Zealand Plant Protection, 2008)
Rice weevils (Sitophilus oryzae) are important stored product pests of grains throughout the world and can lead to complete rejection of seed lots Fecundity and fertility of females are central to their ability to populate and destroy grains Pest control with insecticides on food grain crops is undesirable causing rejection of seed lots that contain residues Therefore any information contributing to alternative management or enhancement of existing control techniques is important Behavioural factors have been found to influence fecundity and fertility of this pest A recent study found a reduction in fecundity and fertility in females that are exposed to multiple males However the mechanism behind this is unknown This experiment examined how male density affected female feeding copulation and oviposition in S oryzae under three sex ratios 11 51 and 101 (malefemale) Results show that copulation duration significantly increased with increasing male density (P